ACTUALIZATION OF RELIGIOUS MODERATION THROUGH THE ROLE OF SPIRITUAL STORES AND COMMUNITY FIGURES IN LOMBOK - Afkarul Azmi; Fahrudin Fahrudin; Agus Fakhruddin (EDURELIGIA: Jurnal Pendidikan Agama Islam, 2024)
The purpose of this study described the roles of religious, and community figures as the vanguard in actualizing values of religious moderation. This study also described  forms of religious harmony in Lombok society. This study used a qualitative and descriptive analysis method based on best practices through interviews, observations, and document studies as data collection techniques. Data research was analyzed through data reduction, data display, data conclusion, and data verification. The results of this study indicated the success of religious figures and community figures through their crusial roles as educator in providing an attitude of tolerance, facilitator in facilitating religious activities, coordinator in building harmonious communication, and mediators in resolving various problems between religious communities. The role of the spiritual, and community figures also has an impact on harmony in society in terms of religious harmony, social harmony, and cultural harmony as a form of actualization of religious moderation in Lombok society.